Prevalence of Anosmia & Ageusia in confirmed COVID-19 patients at teaching hospitals of District Bannu and Swat, Pakistan. - Mohammad Iqbal; Sahibzada Fawad Khan; Khan, Sohail; Ahmad, Wasim (International Journal of Endorsing Health Science Research, 2021)
Background: Recent evidence suggests olfactory and gustatory sensory deficits among Coronavirus Disease 2019 (COVID-19) patients. It is important to assess the occurrence of anosmia and ageusia among infected individuals as it may be the potential symptom and assist in controlling the viral load. The objective of the present study was to determine the prevalence of ageusia and anosmia among COVID-19 patients admitted to the teaching hospitals of District Bannu and Swat-Pakistan. Methodology: This retrospective cohort study was conducted between April to November 2020. A total of 100 confirmed COVID-19 cases, tested through polymerase chain reaction (PCR), were included in the study. Data including gender, age, smoking status, recent travelling history, nasal and paranasal disorder (NPND) history and COVID-19 severity were obtained from the patients’ records. The symptomatology, including frequency of anosmia and ageusia was recorded. Results: Out of 100 patients, 43.75% of patients had anosmia and 31.25% had ageusia, while 68% of patients were presented without olfactory and gustatory dysfunction. Most of the enrolled patients had no recent travel history (91.46%) and none of them were asymptomatic. Moreover, 88% of patients with a previous history of NPND did not have olfactory and gustatory dysfunction. Various characteristics features, including recent travel history, smoking, gender and disease severity, were significantly associated with anosmia and ageusia. Conclusion: The COVID-19 patients were exclusively suffering from ageusia and anosmia. It can be concluded that amongst asymptomatic-to-mild disease severity patients, the existence of smell and taste might be an important differential demonstration for the apprehension and analysis of COVID-19.